VALUATION OF COMPLEX FORMS OF PERCEPTION IN ADOLESCENTS WITH BEER ALCOHOLIZATION - Galina Albertovna Novikova; Andrey Gorgonevich Solovyev; Lyubov Ivanovna Gubareva; Lubov Albertovna Novikova; Elena Victorovna Agarkova (Наука. Инновации. Технологии, 2022)
For the purpose of an assessment of difficult forms of perception of teenagers at beer alcoholization we conducted examination of 152 pupils of comprehensive schools of Arkhangelsk. It is established that to teenagers at beer alcoholization violations in difficult forms the perceptions which are showing in decrease in accuracy of perception of the sizes, space and time that can testify to defeat of parietal and temporal departments of a brain and violations in visual, vestibular, motive and skin feelings are observed; thus, the alcoholization is higher, the these violations that can be used as a marker for early diagnostics of formation of beer dependence are more strongly expressed.